Bacterial community assembly in activated sludge: mapping beta diversity across environmental variables. Issue 6 (19th October 2016) - Isazadeh, Siavash; Jauffur, Shameem; Frigon, Dominic
Abstract: Effect of ecological variables on community assembly of heterotrophic bacteria at eight full‐scale and two pilot‐scale activated sludge wastewater treatment plants (AS‐WWTPs) were explored by pyrosequencing of 16S rRNA gene amplicons. In total, 39 samples covering a range of abiotic factors spread over space and time were analyzed. A core bacterial community of 24 families detected in at least six of the eight AS‐WWTPs was defined. In addition to the core families, plant‐specific families (observed at <50% AS‐WWTPs) were found to be also important in the community structure. Observed beta diversity was partitioned with respect to ecological variables. Specifically, the following variables were considered: influent wastewater characteristics, season (winter vs. summer), process operations (conventional, oxidation ditch, and sequence batch reactor), reactor sizes (pilot‐scale vs. full‐scale reactors), chemical stresses defined by ozonation of return activated sludge, interannual variation, and geographical locations. Among the assessed variables, influent wastewater characteristics and geographical locations contributed more in explaining the differences between AS‐WWTP bacterial communities with a maximum of approximately 26% of the observed variations. Partitioning of beta diversity is necessary to interpret the inherent variability in microbial community assembly and identify the driving forces at play in engineered microbial ecosystem. Abstract : Effect of ecological variables on community assembly of heterotrophic bacteria at eight full‐scale and two pilot‐scale activated sludge wastewater treatment plants (AS‐WWTPs) were explored by high‐throughput pyrosequencing of 16S rRNA gene amplicons. A core bacterial community of 24 families present at most wastewater treatment plants was defined, and a numbers of highly abundant plant‐specific families (observed at <50% AS‐WWTPs) were identified. Among the range of environmental variables assessed, influent wastewater characteristics and geographical locations contributed the most in explaining the differences between AS‐WWTP bacterial communities with a maximum of approximately 26% of the observed variations that could be explained.